2013
DOI: 10.3390/en6073392
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Storage System Sizing Method for Wind Power Integration

Abstract: Combining an energy storage system (ESS) with a wind farm is an effective way to increase the penetration rate of wind power. ESS sizing is an important part in wind farm planning nowadays. In this paper, a basic method for determining the optimal capacity of an ESS integrated with a wind power generator to meet the requirements of grid integration is presented. With the proposed method, the necessary ESS capacity which can provide the best benefits between the regulation effects and energy storage size was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…And we also relates the average wind power since that value can affect level of the WP fluctuation as described in Equation (5). From these considerations of average wind speed and capacity of an ESS in the formulation of parameter k d , we can adapt this formulation to different size of WT or ESS using above Equation (8). Figure 3 illustrates the ESS control strategy that was previously introduced in [24].…”
Section: Proposed Control Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…And we also relates the average wind power since that value can affect level of the WP fluctuation as described in Equation (5). From these considerations of average wind speed and capacity of an ESS in the formulation of parameter k d , we can adapt this formulation to different size of WT or ESS using above Equation (8). Figure 3 illustrates the ESS control strategy that was previously introduced in [24].…”
Section: Proposed Control Strategymentioning
confidence: 99%
“…Energy storage system (ESS) can be used to mitigate the renewable power fluctuation, shave the load peak, and level the load, as discussed in [7][8][9]. Some authors [10] also studied single or hybrid ESSs and reported that the performance was improved when using a hybrid ESS compared to a single ESS, even when compared to a previous study that investigated a single type ESS control [11].…”
Section: Introductionmentioning
confidence: 99%
“…C E = E max E /u min = P max e × ∆t/u min (6) Noted that the main effect of the ESS is to compensate for the power deviation from the forecast; as a result, the largest forecasting error is the total capacity of the ESSs.…”
Section: Electrical Energy Forecastingmentioning
confidence: 99%
“…Studies [3,4] show that an optimal planning of locations and sizes of ESSs in power systems can reduce a power system's costs and enhance a its reliability and power quality. A novel method has been presented in [5] for designing an energy storage system dedicated to the reduction of the uncertainty of short-term wind power forecasts up to 48 h. Wang et al in [6] proposed a determination methodology for optimizing the capacity of an ESS that enables a wind power generator to meet the requirements of grid integration. To improve regulation effects, the segmentation method and automatic segmentation…”
Section: Introductionmentioning
confidence: 99%
“…As the power grid fails to accommodate the fast deployment of wind power, wind curtailment phenomena occur frequently, which is against the original intention of "energy conservation and emission reduction". In order to enhance the controllability of wind farms, matched energy storage devices are constructed so as to facilitate the wind power integration, which has become the consensus within this field [6][7][8]. In [9], the authors used an energy storage system (ESS) to improve the wind energy integration and grid voltage stability.…”
Section: Introductionmentioning
confidence: 99%